Empowerment and Position of Gaddis Women in Ravi River Basin in Himachal Pradesh - Nikesh Sharma (East Asian Journal of Multidisciplinary Research, 2022)
For the indigenous community, empowerment of women is critical to the development of their society and the Women have no right to inheritance as per the traditional laws. The women works equally with her husband in agricultural work expect for pouching. They also take part in all social, religious and ritual activities. More than 90% of Gaddis women are Empowered to spend money, independently without seeking permission from male, members of the family, and also, to access health care services for themselves and their children.   Girls, as a daughter, enjoyed full freedom like those of boys and one could notice no discrimination between boys and girls. In fact, the Gaddis woman has been expert in all these. The educated and employed wife’s status is better than uneducated and unemployed wife’s. Although, Gaddis society is patriarchal, the family revolves around the mother. Women play a central role in the family, providing labor for the various tasks with regard to the livestock, the land and the household (L.S. Thakur, 2002).